Walking That Fine Line: Doulas as Overseers of Evidence-based Practice. (April 2023) - Henley, Megan M.
Doulas provide individualized support during labor and childbirth. Research has consistently shown that having doulas support increases positive physical and psychological outcomes. Professional medical organizations have begun to recognize the evidence showing the positive effects of doula support. Even though professional organizations recommend doulas to reduce non-medically indicated treatments such as overuse of cesarean delivery, many practitioners uphold their authority to intervene as they see necessary. I utilize interviews with 25 doulas to explore how doulas use scientific evidence to ensure that women receive appropriate care. Results indicate that doulas do not think that many obstetricians follow evidence-based practices; doulas feel compelled to serve as overseers who remind medical staff about the clinical guidelines. In addition, doulas use evidence to prepare mothers to confront providers. I argue that while doulas can help close gaps, obstetric medicine needs to implement evidence-based strategies more systemically to improve care for all women.